PERCEPTIONS AND LOYALTY: THE ROLE OF HALAL LABELS IN THE COSMETIC MARKET - El Shinta (GREET, 2024)
This study explores the role of halal labels in shaping consumer loyalty within the cosmetics industry, with a particular focus on trust, perceived quality, and ethical value alignment. Adopting a qualitative approach, data were collected through in-depth interviews, retail observations, and case studies of established halal-certified cosmetic brands in Indonesia. Thematic analysis revealed that halal labels significantly contribute to consumer loyalty by reinforcing brand trust, validating product quality, and resonating with cultural and religious values. Interestingly, halal certification also attracted non-Muslim consumers, who perceived it as an indicator of product safety, ethical sourcing, and environmental responsibility. These findings highlight the cross-cultural appeal of halal cosmetics and suggest that brands can leverage halal certification as a strategic marketing asset. Practical implications include the need for transparent communication of halal standards, collaborations with reputable certification bodies, and the integration of ethical narratives in brand positioning. Future research is encouraged to examine loyalty trends longitudinally and explore the role of digital marketing in promoting halal-certified products across diverse consumer segments.